ANALISIS YURIDIS PERMENDAGRI NO 04 TAHUN 2007 DAN PANDANGAN HUKUM ISLAM TERHADAP PEMANFAATAN TANAH BENGKOK - Akhmad Rudi Maswanto (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
The question of being an object in this paper is about the reconstruction of land law in the view of Islamic law, how Islam also participates in the mapping of the fairness of the money, which is for the welfare of the ummah. In the case of the use of twisted land (land belonging to village government) is the question of whether the land is solely for the sake of the provision of the salaries of village officials or more than that for the purpose of Village development. This research is done using a qualitative approach with the intent to know how the existence of the information Village program in the view of rural residents is the target of the program. The data collection process relies on observation methods and interviews.